Autoantibodies to thyroid hormones: the role of thyroglobulin - ERREGRAGUI, K (Blackwell Science Inc, 1996)
Autoantibodies against thyroid hormones (THAA) are frequently detected in the sera of patients with thyroid disorders together with autoantibodies against thyroglobulin (TGAA). THAA are considered to be a subset of TGAA, but alternative possibilities have not been excluded. We hypothesize that if THAA arise through an immune response to iodothyronines carried by circulating thyroglobulin (hTg), THAA should be found together with autoantibodies against the peptide backbone of hTg (TPAA) close to the hormone-forming sites. We measured TPAA in 178 serum samples, obtained from healthy subjects and patients with thyroid disorders, using two hormone-forming peptides isolated from hTg. The occurrence of TPAA was much lower than that of TGAA. Autoantibodies to the hormone-rich peptide, P3, were significantly more common than autoantibodies to the hormone-poor peptide, P1 (111/178 = 62.3% for TGAA versus 21/178 = 11.8% for anti-P3 TPAA and 7/178 = 3.9% for anti-P1 TPAA). The presence of autoantibodies to thyroid hormones was investigated in 25 TPAA(+) and 26 TPAA(−) sera. THAA were found more frequently in TPAA(+) sera (10/25 = 40% for TPAA(+) and 4/26 = 15.3% for TPAA(−)). Correlation analysis shows that the anti-P3, but not the anti-P1 binding activity, correlates positively with the THAA-binding activity (P < 0.001 for anti-T4 THAA; P< 0.01 for anti-T3 THAA). Specificity of anti-P3 TPAA indicates that a subset of the anti-P3 antibodies is directed against the thyroid hormone moiety and another subset is directed against the peptide backbone near the hormone-forming peptide, according to our hypothesis. These results indicate that the THAA response is an anti-hTg response directed, in a significant number of cases, against the hormone-forming site included in the P3 peptide. This response seems to be elicited by either native hormone-rich hTg or by hTg fragments.